OPTIMALISASI FUNGSI LABORATORIUM KIMIA DALAM PROSES PEMBELAJARAN DI SMA NEGERI 9 SEMARANG - Rahmawati, Atika Sis; Hidayah, Fitria Fatichatul (Universitas Muhammadiyah Semarang, 2017)
Optimization of the use of chem lab have a major influence to successful learning chemical .The optimization of the use of chem lab was calculated by the extent towhich the intensity of use , organizing all the organizational structure of thelaboratory and organizing student participants lab work .The study aimed toidentify the optimal function chem lab in learning in schools 9 semarang .Asubject of study include chemical and teachers 2 x 50 students in schools andclass xi-mia 9 semarang .Data gathered by the questionnaire , observation ,interview semistruktur and documentation with the descriptive sample purposivequalitative analysis The results of the study based on recapitulation thequestionnaire the levels of trust school tuition to the use of laboratory in thecategory of good, attitude and acceptance of school tuition to masses of in thelaboratory in the category of good, and readiness perserta students withÂ regardto masses of in the laboratory in the category of good. Keywords: optimization, the use of laboratory, learning chemical